EFEKTIVITAS MODEL DISCOVERY LEARNING DAN INQUIRY TERHADAP KETERAMPILAN BERPIKIR KRITIS PADA MATA PELAJARAN MATEMATIKA SISWA KELAS 5 SD - Joko Subiono; Wasitohadi Wasitohadi (Jurnal Karya Pendidikan Matematika, 2020)
This research aims to tested the Discovery Learning model is more effective than Inquiry Learning model seen from critical thinking skills of mathematic for students grade 5. This research used the Quasi experimental design. The sample of research is 24 students grade 5 at Sidorejo Lor 03 elementary school as experimenta class and 24 students at Sidorejo Lor 02 as control class. The variable of the research is Discovery learning and Inquiry Learning as X variabel and critical thinking as Y variable. The techique data analysis used normality datatest, homogenity test, t-test, and hypothesis test. The result of t-test score is sig (2-tailed) 0,003 ˂ 0,005 and the conclusion that Ho is refused and Ha is accepted, so the implementating of Discovery learning model is better than Inquiry Learning model seen from critical thinking skills of mathematic grade 5 of students elemtary school, difference in effectiveness model for critical thinking skills supported with the result of post test both of the classes is 81 experimental class and 72 control class.